The employee union as an anti-corruption instrument - Gaffud, Dolores L. (1994)
The employees of the public enterprise discussed here formed one not solely to protect their own interests but also to uphold the well-being oft heir agency. The processes they followed and the results of their efforts are the subject of this article.
Keywords: Corruption investigation; Government agencies -- Corrupt practices